Suriname : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Suriname. (IMF Staff Country Reports; Country Report ;, 2007)
This 2007 Article IV Consultation highlights that aided by favorable external conditions and an improvement in macroeconomic management, Suriname's economic performance has improved in recent years. Since 2002, the central government deficit has declined sharply, leading to a substantial decrease in public debt as a share of GDP. Monetary policy has focused on reducing inflation, while the central bank has become more independent. In 2006, macroeconomic performance was better than anticipated, benefiting from a continued favorable external environment. The outlook for 2007 looks broadly positive.